The political principles of Senator Barry M. Goldwater as revealed in his speeches and writings : a source book - Goldwater, Barry M. (Barry Morris), 1909-1998 (Edwin Mellen Press, 2012)
This book presents a selected compilation of Senator Barry M. Goldwater's speeches and writings from the 1950s to the 1990s. Arranged chronologically, these primary source documents reveal the Senator's position on deficit spending, defense, politics, foreign policy, Gay Rights, Native Americans, Civil Rights, the news media, natural resources, constitutional rights, freedom, evangelical preachers, and other topics dealing with the making of modern American political principles. With a comprehensive introduction, appendix of related speeches and writings, and list of suggested readings, this v.